Relative levels of Beet necrotic yellow vein virus in susceptible to resistant genotypes of sugar beets during growing season - S.B. Mahmoudi (Sugar Beet Seed Institute, 2012)
In order to study the trend of BNYVV concentrations during growing season, 6 cultivars including Dorohtea, Laetitia(as resistant cultivars), Zarghan (as a tolerant cultivar), Shirin (as a susceptible cultivar), F2-93 (an F2 population with 75 % Rz2 gene) and BC1-261-99 (a population with 25% Rz2 gene) were used. The cultivars were planted in split plot based on a randomized complete block design with 4 replications. Main plots were four different dates of sampling (2, 3 and 4 months after planting and harvesting time) for ELISA. In each sampling date, 12 plants were selected randomly from each plot for DAS-ELISA. The experiment was re-peated for two years in a naturally rhizomania infested field. Mean of ELISA values was increased in the initial sampling dates and then decreased gradually up to the end of the season. Based on the trend of ELISA values, logical grouping of the genotypes was happened in the second and third sampling dates in the first and second years, respectively. The results showed that reaction of sugar beet genotypes to the disease could be identified 3-4 months after planting and that detecting infested fields in this period would be reliable.